2016
DOI: 10.1016/j.gyobfe.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Do maternal pushing techniques during labour affect obstetric or neonatal outcomes?

Abstract: The low methodological quality of the studies and the differences between the protocols do not justify a recommendation of a particular pushing technique. Further studies appear necessary to study outcomes with each of these techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
1
14
0
5
Order By: Relevance
“…6 11 Only one trial included multiparous women 6. A recent review points out that co-interventions varied between studies,16 as did the mother’s position during the second stage of labour. One study left position to the woman’s choice;6 two others mandated a specific position: dorsal decubitus position in one11 and semirecumbent in the other 5.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…6 11 Only one trial included multiparous women 6. A recent review points out that co-interventions varied between studies,16 as did the mother’s position during the second stage of labour. One study left position to the woman’s choice;6 two others mandated a specific position: dorsal decubitus position in one11 and semirecumbent in the other 5.…”
Section: Background and Significancementioning
confidence: 99%
“…One study left position to the woman’s choice;6 two others mandated a specific position: dorsal decubitus position in one11 and semirecumbent in the other 5. Globally, the quality of the randomisation was not good 16. One study reported using sealed envelopes,6 one failed to specify the kind of envelope used,11 and the last one did not specify the mode of randomisation 5.…”
Section: Background and Significancementioning
confidence: 99%
“…O puxo dirigido é estimulado independentemente da vontade de puxar. A mulher é solicitada a inspirar profundamente no início da contração e a utilizar a apneia expiratória durante um período de 10 a 30 segundos, associada ao esforço com contração abdominal e diafragmática (com a glote fechada) numa frequência de três a quatro puxos em cada contração (Álvarez-Burón e Arnedillo-Sánchez, 2010; Barasinski et al, 2016).…”
Section: Puxo Dirigido Durante O Parto (Manobra De Valsalva)unclassified
“…Segundo Barasinski et al (2016), o puxo dirigido, também chamado de "manobra de Valsalva", é amplamente utilizado nos países ocidentais, mas a origem desta prática obstétrica é obscura e provavelmente foi desenvolvida com a disseminação dos partos fórcipes, mas sem dados científicos convincentes para apoiá-lo. De acordo com o MS, embora sem registros oficiais, ainda é uma prática muito comum na assistência à mulher no trabalho de parto.…”
Section: Puxo Dirigido Durante O Parto (Manobra De Valsalva)unclassified
See 1 more Smart Citation